Pengaruh Aromaterapi Lavender terhadap Penurunan Tekanan Darah pada Ibu Hamil dengan Hipertensi Gestasional - Desviola Ariani; Renny Adelia Tarigan; Savitri Gemini (Lembaga Pengembangan Kinerja Dosen, 2026)
Gestational hypertension is one of the leading causes of maternal mortality in Indonesia. Non-pharmacological interventions such as lavender aromatherapy have gained attention as complementary therapies due to their natural properties and minimal side effects. This study aims to evaluate the effect of lavender aromatherapy on blood pressure among pregnant women with gestational hypertension. The research employed a quasi-experimental design using a one-group pretest-posttest approach. A total of 15 participants meeting the inclusion criteria received an intervention consisting of lavender aromatherapy inhalation for 10–15 minutes. The results showed a decrease in mean systolic blood pressure from 141.53 mmHg before the intervention to 139.27 mmHg after the intervention. However, the mean diastolic blood pressure slightly increased from 90.20 mmHg to 90.27 mmHg. The reduction in systolic pressure indicates a potential relaxation effect of lavender, likely mediated through parasympathetic nervous system stimulation. Although the change in diastolic pressure was minimal and not clinically significant, these findings support the use of lavender aromatherapy as a supportive approach in managing blood pressure in pregnant women with gestational hypertension. This complementary therapy is expected to enhance maternal healthcare, particularly in improving comfort and reducing stress during pregnancy.